Pengembangan Multimedia Interaktif Berbasis Kearifan Lokal Ruwatan Rambut Gimbal untuk Pembelajaran Ilustrasi dan Penguatan Pendidikan Karakter di SMP - Savitri Wukirasih Milandari (Alpatih Harapan Semesta, 2026)
The tradition of ruwat rambut gimbal is a local wisdom of the Dieng community that contains character values ​​and has the potential to be used as a culture-based learning resource. This study aims to develop interactive multimedia based on the ruwat rambut gimbal tradition for illustration learning for grade VIII junior high school students by integrating the values ​​of Strengthening Character Education (PPK). The study used the Research and Development (R&D) method with the ADDIE model. The results showed that multimedia integrates religious values, independence, mutual cooperation, responsibility, social care, and environmental care. The validation results obtained a percentage of 91.11% from material experts and 95.78% from media experts with a very feasible category. The trial on 32 students obtained a percentage of 94.04% with a very feasible category, indicating that multimedia is able to support illustration learning while introducing local culture and character values. The developed interactive multimedia is suitable for use as a local culture-based Arts and Culture learning medium.